Multi-scale models for the optimization of batch bioreactors - Liew, Emily; Nandong, Jobrun; Samyudia, Yudi (IFAC, 2012)
In this paper, we propose multi-scale models for a batch bioreactor, which are developed by expanding the so-called Herbert’s Microbial Kinetics (HMK) concept so that the effects of mixing conditions are incorporated via the inclusion of the aeration rate and stirrer speed into the microbial kinetics. By using the multi-scale models, we are able to optimize the batch bioreactor’s performances, i.e. yield and productivity, by adjusting the aeration rate and stirrer speed. Simulation and experimental studies on a batch (fermentation) bioreactor demonstrate the application of this approach, whereby the integration of the expanded HMK model with the Computational Fluid Dynamics (CFD) model of mixing, which we call it as a Kinetics Multi-Scale (KMS) model, is able to predict the experimental values of yield and productivity of the batch fermentation process accurately (with less than 5% errors).